Vaḷḷuvattil meypporuṭ cuvaṭukaḷ - Taṇṭapāṇi Tēcikar, Ca., 1906- (Tirukkuṛaḷ Ārāycci Nitiya veḷiyīṭu, 1980)
On the concept of philosophy as expounded in Tirukkuṟaḷ, ancient Tamil didactic verse work by Tiruvaḷḷuvar.